INVENTARISASI HAMA TANAMAN LENGKENG (Dimocarpus longan Lour.) DI DESA PETAPAHAN, KECAMATAN TAPUNG, KABUPATEN KAMPAR - Juliarni, Juliarni; Wirawan, Purnama; ua, Maruli; Kurniawan, Riansyah; Iznih Sinaga Bonor , Nabila (Universitas Muhammadiyah Bengkulu, 2025)
The cultivation of longan in Indonesia holds strong potential due to high consumer demand, favorable environmental conditions, and the availability of varieties well adapted to the local climate. However, pest attacks remain a major constraint, often reducing both the quantity and quality of fruit production. This study aimed to inventory the pest species associated with longan cultivation. The research was conducted through field surveys, with sampling locations determined using a purposive random sampling method. Insect specimens were collected directly by hand and preserved in vials containing 75% alcohol. The specimens were then examined under a microscope and documented. Observed parameters included the diversity index, evenness index, and dominance index, with data analyzed descriptively. The results showed that the primary pest attacks targeted the leaves and flowers of longan plants. A total of eight pest species belonging to two families—Scarabaeidae and Coreidae—were recorded. The pest diversity index (H’) was categorized as moderate (1.8), the evenness index (E) was high (0.9), and the dominance index (C) was low (0.2).